Lung resident mesenchymal cells isolated from patients with the Bronchiolitis Obliterans Syndrome display a deregulated epigenetic profile - Serena Vella (Nature Portfolio, 2018)
Abstract Bronchiolitis Obliterans Syndrome is the major determinant of the graft function loss after lung transplantation, but its pathogenesis is still incompletely understood and currently available therapeutic strategies are poorly effective. A deeper understanding of its pathogenic mechanisms is crucial for the development of new strategies to prevent and treat this devastating complication. In this study, we focused on the mesenchymal stromal cells, recently recognized as BOS key effectors, and our primary aim was to identify their epigenetic determinants, such as histone modifications and non-coding RNA regulation, which could contribute to their differentiation in myofibroblasts. Interestingly, we identified a deregulated expression of histone deacetylases and methyltransferases, and a microRNA-epigenetic regulatory network, which could represent novel targets for anti-fibrotic therapy. We validated our results in vitro, in a cell model of fibrogenesis, confirming the epigenetic involvement in this process and paving the way for a new application for epigenetic drugs.